The Statistical Analysis and Forecasting of Ukraine’s Export - Golubova, G. V. (Statistics of Ukraine, 2018)
In the article the author determined the main directions of foreign economic activity of the country and was established that the main course for Ukraine is foreign trade and international investment activity. The author done analysis of the foreign trade balance of Ukraine for 2017 shows the passive balance of trade balance. The analyzed indicators of foreign trade balance show that in 2017 Ukraine economy was opened (0.93), i. e. it is risk-prone, import-dependent (46.8%), the share of exports in the total amount of the gross domestic product was 45.8%, the coefficient of coverage the export over import was 98%. The calculated coefficient of the international intraspecific specialization of the country shows that Ukraine is import-dependent from the following groups of goods and services: works of art (–75,5%), polymer materials, plastics and articles (–75,0%), means of land transport, aircraft, floating means (–68.4%), optical and photographic equipment (-59.9%), state and government services (–99.5%), royalties (–83.3 %), financial services (–74.2%). The author was determined and substantiated the factors influencing the tendencies of export development of Ukraine, which were the basis of correlation-regression analysis. The export links with all selected factors based on the pair correlation coefficients are analyzed. A high correlation was found between exports with imports (0.987), a rather close but inverse relationship with the US dollar (–0.887), a significant and direct correlation between export of FDI to Ukraine (0.693) and a noticeable but inverse relationship exports with GDP (–0.693) and consumer price index (–0.690). During the analysis, the author built two regressive models of export dependence from import transactions and under the influence of the exchange rate. The author substantiated the effect of the fluctuation of the US dollar exchange rate on exports of goods and services, and predicted Ukraine’s exports in the short period.